Preventing antisocial behavior : interventions from birth through adolescence - MacCord, Joan; Tremblay, Richard E. (Guilford, 1992)
Over the ensuing years, a variety of approaches have been used in an attempt to prevent children from following the path that leads to criminal behavior or to remedy that behavior before they become habitual criminals. The unique contribution of the 20th century, we believe, has been method. By introducing experimental approaches to the study of intervention strategies, enduring results can issue from programs that have failed to achieve their therapeutic goals. The studies we selected for this work vary in the ways in which science has been applied. . . . We hoped that by selecting variety in method, this book would provide readers with the opportunity to consider evaluation techniques while also enabling some readers to develop strategies for evaluating their own programs. Our intention was not only to stimulate clearer consideration of evaluation strategies but also to show some of the imaginative interventions that have been designed to assist children at every age. The chapters include biological, social, emotional, and cognitive approaches. We have included interventions aimed at infants, at children, and at adolescents. The order of presentation follows, roughly, a developmental perspective in which the age of earliest intervention accounts for placement. Experience seems to show, however, that even effective prevention strategies will miss some of the people some of the time. That being the case, we are likely to need a variety of programs in order to help the variety of children in need of assistance. The chapters that follow describe programs that intervene in families, in schools, and in communities. Some target populations at risk, while others focus on individuals